Effect of exercises on system Pilates on psychoemotional statuses of women of the first age of maturity. - Zagura F.I; Lesko O.M.; Kozibroda L.V (Kharkov National Pedagogical University, 2010)
Effect of a system on improving of the fissile vital activity of women of 21-35 years is exhibited. 10 instructors participated in experiment high-performance professional work. 26 women with approximated performances of physical readiness also have taken part. The program on 4 training improving levels is presented. Assimilation of the given program has taken 5 months. It is revealed improvings a level of psychoemotional statuses: state of health, activity and mood. It is offered to conduct occupations in a mode of 2-3 times for a week. It is necessary to ensure occupations by the methodical information in the different form (the literature, video data, the Internet, the consultative help, etc.). The possible form of independent occupations under condition of possession of determined knowledge.